2015
DOI: 10.1111/jcmm.12490
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐dimorphic regulation of DJ1 and its interactions with metabolic proteins in streptozotocin‐induced diabetic rats

Abstract: Regulation of DJ1 is associated with a number of human diseases. To determine the involvement of DJ1 in progression of diabetes in a genderdependent manner, we investigated its tissue-specific expression in streptozotocin (STZ)-induced diabetic male and female rats in this study. In animal experiments, females showed greater susceptibility towards developing diabetes because of lower insulin secretion and higher blood glucose levels as compared to male diabetic rats upon exposure to STZ. Immunoblotting confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Hydroxymethylglutaryl‐CoA lyase is a mitochondrial enzyme that has an indispensable role in the formation of ketone bodies (acetoacetate), which are the precursors for glyoxylate intermediates such as methylglyoxal (MG) (Chaudhari, Kim, & Yun, ). We found a 76‐fold increase in the activity of this protein in the diabetic pancreas, which was suppressed by PTS treatment (0.05‐fold).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxymethylglutaryl‐CoA lyase is a mitochondrial enzyme that has an indispensable role in the formation of ketone bodies (acetoacetate), which are the precursors for glyoxylate intermediates such as methylglyoxal (MG) (Chaudhari, Kim, & Yun, ). We found a 76‐fold increase in the activity of this protein in the diabetic pancreas, which was suppressed by PTS treatment (0.05‐fold).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some studies have shown that with the ascending of blood glucose, the content of DJ-1 was increased to inhibit the expression of ROS. 27,28 . In addition, the renal protective effects in diabetic rats might be enhanced by the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Although hyperglycemia was less pronounced, diastolic dysfunction was more pronounced in STZ-induced diabetic female mice [52].Reduced circulating estradiol levels and imbalance in renal estrogen receptor expression accelerate the progression of diabetic nephropathy [53].Insulin sensitivity and susceptibility to diabetes are indeed associated with sex differences [54][55][56][57].However, it has also been reported that establishing equivalent diabetes in male and female Nos3-deficient mice results in a comparable onset of diabetic kidney injury [58].…”
Section: Discussionmentioning
confidence: 99%